Horvát integráció magyar szemmel - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2009)
The prior aim of the paper is to present the next station of the enlargement process of the European Union, the chances and challenges of the Croatian accession after the democratic transformation. The study is about to investigate how an old-and-new state is searching for its identity, and what a bumpy road does it have to cope with in order to get to be part of the European space. Two phases of the whole integration process could be separated. The first term is from the declaration of independence (26 June 1991) till the death of president Franjo Tudjman (10 Dec 1999), when beyond building a democratic country and state, Croatia also tried to identify and manage the priorities of its independent foreign policy. The next phase is mainly characterised by the development and deepening of relations between the EU and Croatia from the death of the president on, when the substantial investigations started between Croatia and the European Union, and are still in progress.